Effect of liquid seaweed fertilizer of Sargassum wightii grev. on the growth and biochemical content of green gram (Vigna radiata (L.) R. wilczek) - Ashok Kumar, N; Vanlalzarzova, B; Sridhar, S; Baluswami, M (Recent Research in Science and Technology, 2012)
Intensive investigations were made on the efficiency of Liquid Seaweed Fertilizer (LSF) obtained from the brown seaweed Sargassum wightii Grev. on the germination, growth and biochemical constituents of green gram (Vigna radiata (L.) R. Wilczek) under laboratory conditions and in pots. The seeds that are soaked for 6 hrs duration at lower concentrations such as 0.5% and 1.0% showed faster germination compared with the seeds that are soaked at higher concentration (2.0%) for long durations (12 hrs and 24 hrs). In pot studies, both the shoot length and root length were found to be increased as the concentration of LSF increases, but at high concentration i.e. at 2.0% concentration the growth was slightly reduced. Of the two different types of applications i.e. foliar and root applications, the foliar application was found to be more effective in determining the growth of the plant than the root application. Plants received with 1.0% concentration of LSF as foliar spray showed more shoot and root length, early flowering and more number of pods. The biochemical analysis of the experimental plants showed that the foliar treated plants showed more photosynthetic pigments compared to root treated plants, whereas the accumulation of total protein, total carbohydrate and total lipid content was found maximum in root treated plants than the foliar treated plants.